LEBANON, IDENTITY, DISLOCATION, AND MEMORY - Salameh, Franck (The Levantine Review, 2012)
Review of: Dalia Abdelhady, The Lebanese Diaspora; The Arab Immigrant Experience in Montreal, New York, and Paris (New York and London: New York University Press, 2011), pp. 198, paperback, ISBN 978-0-8147-0734-0 Craig Larkin, Memory and Conflict in Lebanon: Remembering and Forgetting the past. (New York and London, Routledge: Taylor&Francis Group, 2012), pp. 226, hardcover, ISBN 978-0-415-58779-2